2017
DOI: 10.1177/0312896217712334
|View full text |Cite
|
Sign up to set email alerts
|

Does board independence substitute for external audit quality? Evidence from an exogenous regulatory shock

Abstract: Exploiting the passage of the Sarbanes–Oxley Act (SOX) as an exogenous regulatory shock, we investigate whether board independence substitutes for external audit quality. Based on over 14,000 observations across 18 years, our difference-in-difference estimates show that firms forced to raise board independence are far less likely to employ a Big 4 auditor. In particular, board independence lowers the propensity to use a Big 4 auditor by approximately 38%. Firms with stronger board independence enjoy more effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 59 publications
(26 reference statements)
3
29
0
2
Order By: Relevance
“…By choosing an exogenous and largely unexpected event, we assess the governance–performance relationship before the performance can affect the composition of the board. That is, the research design controls for the implicit endogenous effect (Aldamen et al ., ; Gippel et al ., ; Aldamen and Duncan, ; Jiraporn et al ., ; Kan and Gong, ).…”
Section: Data Variables and Methodologymentioning
confidence: 99%
“…By choosing an exogenous and largely unexpected event, we assess the governance–performance relationship before the performance can affect the composition of the board. That is, the research design controls for the implicit endogenous effect (Aldamen et al ., ; Gippel et al ., ; Aldamen and Duncan, ; Jiraporn et al ., ; Kan and Gong, ).…”
Section: Data Variables and Methodologymentioning
confidence: 99%
“…Srinidhi, He, and Firth () argued that the Type II agency problem has not been well documented in the existing literature, and revealed that the US family firms with stronger boards are more likely to appoint specialist auditors, demand greater audit efforts, and report higher quality earnings in the post‐SOX era. Jiraporn, Chintrakarn, Tong, and Treepongkaruna () viewed board independence as a substitute for external audit quality. The findings of Srinidhi et al () implied that strong boards mitigate Type II agency concerns by upholding the interests of diverse outside investors relative to the family investors.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
“…The potential impact of board independence on auditor choice has been investigated by a number of studies in the audit literature (e.g. Beasley and Petroni, 2001;Jiraporn et al 2018). While Beasley and Petroni (2001) found evidence of a positive relation between board independence and the selection of a 'Big" audit firm, Jiraporn et al (2018) found no evidence of such a relation.…”
Section: Board's Independencementioning
confidence: 99%
“…Audit research (e.g., Becker et al 1998;Kim et al 2003;Hsu et al 2015;Ben-Hassoun et al 2018;Jiraporn et al 2018) has long viewed audit firm type (Big 4 vs. non-Big 4) as an influential factor in determining the quality of the financial statements audit. Researchers (e.g., Fan and Wong, 2005;Eshleman and Guo, 2014;Asthana et al 2015;Knechel, 2016) have typically viewed 'Big' audit firms to provide higher quality audit than 'non-Big' firms as a result of their competitive advantages in terms of scale of operations, technical competencies, and market reputation.…”
Section: Introductionmentioning
confidence: 99%